SEMIOTIC ANALYSIS TOWARD THE GREEN ACCOUNTING MEANING BASED MASLAHAH - NURUL ANNISA; SYARIF SYAHRIR MALLE; SUMARNI RANDRIANY (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2022)
This study aimed to know the disclosure and meaning of green accounting-based maslahah in the company's sustainability report. This study was qualitative research using semiotic analysis to analyze the definition contained in symbols or signs in the narrative text on the sustainability report of PT. PP London Sumatra Tbk (Lonsum) in 2020. The study results show that the PT PP Lonsum sustainability report has disclosures about green accounting indicators, either implicitly or explicitly. Protecting the environment (hifdz al bi’ah) can be a trigger for maintaining the five goals of syara'(maqashid sharia).